Instagram in English Language Learning: A Systematic Literature Review - Awal Kurnia Putra Nasution (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
In the ever-growing digital era, social media, especially Instagram, plays a significant role in English language learning. The platform is a multifaceted communication tool and offers visual and interactive features to enhance the student learning experience. This research analyzes the use of Instagram in the context of English language learning through a Systematic Literature Review (SLR) approach. The article selection process involved two stages: selection based on the title and abstract and selection based on the full text. An article search using the keywords "Instagram" and "English language learning" in Science Direct and Google Scholar produced 142 article titles, which were then filtered into 24 articles for further analysis. The conclusion of this research shows that Instagram has great potential in improving English language skills, especially in vocabulary and communication skills. Students' positive response, especially towards the development of writing skills, shows the potential of this platform in language learning contexts. In conventional and distance learning, Instagram is effective in various aspects of learning, including vocabulary, writing skills, grammar, and collaboration. Positive impacts are seen on student skills, creating creative and multimodal learning experiences. The flexibility of Instagram in teaching English for Specific Purposes (ESP), especially collocations and colligations, shows its potential. Future research recommendations include an evaluation of Instagram's effectiveness in teaching specific content and a deeper understanding of the platform's evolving landscape in education.